Upper Esophageal Schwannoma: Rare Differential Diagnosis of Dysphagia - Acharya, Bigyan; Thakur, Binay; Devkota, Mukti; Pandey, Greta; Shrestha, Anup; Chaudhary, Manish (Nepalese Journal of Cancer, 2020)
Esophageal schwannomas are rare primary sub mucosal tumors, 45 cases have been reported so far. We  herein report the 46th case of an esophageal schwannoma from Nepal. A 60-year-old woman presented with progressivedysphagia. Oesophago-Gastro-Duodenoscopy (OGD) showed a sub mucosal mass with mucosal puckering in the upper esophagus; Computed tomography (CT) of the chest showed an upper esophageal mass of size 8x7x6cm3compressing the trachea. Bronchoscopy showed external compression of the mid trachea. The patient under went three incision VATS esophagectomy. Histopathological examination and immunohistochemical (IHC) staining confirmed the diagnosis of schwannoma.